Effects of insect harassment on weight gain and survival in reindeer calves - Helle, T.; Tarvainen, L. (Rangifer, 1984)
Relationships between insect harassment and the weight gain and survival of reindeer calves were studied in two areas in Finland north of the Arctic Circle. The level of insect harassment explained a significant amount of the yearly variation in calf weights determined in autumn or early winter in both areas and directly influenced calf mortality in one of them. The lowest weights and calf percents were experienced in years when a bad winter was followed by a warm summer with severe insect harassment.Råkån vaikutus poronvasojen painonlisåykseen ja eloonjååmiseen.Abstract in Finnish / Tiivistelmd: Rakan (vertaimevat ja porossa loisivat hyonteiset) vaikutusta vasojen painoon ja vasaprosenttiin tutkittiin Alakylan paliskunnassa sekå Kaldoaivi - Paistunturin alueella. Kummallakin alueella rakka selitti huomattavan osan vasojen syyspainojen vuosivaihtelusta ja Kaldoaivi - Paistunturissa se vaikutti suoraan myos vasaprosenttiin. Vasojen painot ja vasaprosentit olivat alhaisimmat vuosina, joina vaikeaa talvea seurasi kuuma, hyonteisille suotuisa kesa.Effekter av insektforstyrrelser på vektøkning og overlevelse av reinkalver.Abstract in Swedish / Sammendrag: Effekter av insektforstyrrelser på vektøkning og overlevelse av reinkalver er studert i to områder av Finland nord for Polarsirkelen. Graden av insektforstyrrelser forklarte en signifikant andel av variasjonene fra år til år i kalvevekter bestemt høst eller tidlig vinter for begge områder. Den virket også direkte inn på kalvedødeligheten i et av områdene. De laveste vekter og kalveprosenter fant man i år der en dårlig vinter ble etterfulgt av en varm sommer med alvorlige insektforstyrrelser.